On the laser beam cutting of metallic hollow sphere structures - Riegel, Harald (2013)
Metal hollow sphere structures (MHSS) represent a group of advanced composite materials. A high geometric reproducibility leads to relatively constant mechanical and physical properties. Therefore MHSS combine the advantages of cellular metals without a big scattering of the material properties. Several joining technologies can be used to assemble single metallic hollow spheres to a interdependent structure like sintering, soldering and adhering. This allows adjusting of variable macroscopic attitudes. A cutting process for MHSS needs to reflect the special characteristic of the composite material. In this paper laser beam cutting is presented as an efficient technology. The small amount of heat being involved during the process results in a small heat affected zone. All investigations were done with MHSS having different macroscopic dimensions (length, width, thickness, joining technology). The experimental work was done by a CO2-laser. The cut depth is governed by the heat input per unit length and the MHSS density. Finite element analysis was used to predict heat flux and temperature level for different geometric parameters of the spheres (diameter, wall thickness). The numerical simulation allows a detailed analysis of the physical process in the zone that is influenced by the laser beam and which can hardly be analysed by measuring technique. The models for the static and transient finite element analysis consider heat conduction and convection